I kissed dating goodbye - Harris, Joshua (Sisters, Or. : Multnomah Publishers, 2003)
1. Dating. (social customs) 2. Dating. (social customs)--Religious aspects.--Christianity. 3. Man.--Woman relationships.
Includes bibliographical references (p. 219-221).
Faculty
Keywords: Dating (Social customs); Dating (Social customs) -- Religious aspects -- Christianity; Man-woman relationships